KAJIAN MENGENAI PENTINGNYA BASIS DATA BAGI SEKOLAH SAAT INI - Krista Surbakti, S.Pd., M.Si (Universitas Quality, 2019)
The database is one of the important components of information systems, as it serves as the information provider base for the users. Application of the database in the information system is called the system database. The database system (database system) is an information system that integrates a collection of data that are interconnected with each other and make it available for multiple applications in an organization.The purpose of database design is to determine the data needed in the system, so that the resulting information can be met well. Databases that have been entered in a storage media can never be accessed without the existence of a software application that is familiar with it, let's say a database-based application software.